2018
DOI: 10.1007/s00134-018-5292-8
|View full text |Cite
|
Sign up to set email alerts
|

MAP of 65: target of the past?

Abstract: Septic shock is defined as sepsis with hypotension refractory to fluid challenge and requiring vasopressor support combined with an increase in arterial lactate reflecting impaired cellular energy metabolism and dysoxia. The use of vasoactive drugs to restore mean arterial pressure (MAP) is strongly recommended by the Surviving Sepsis Campaign [1] and the Task Force of the European Society of Intensive Care Medicine (ESICM) on circulatory shock management and monitoring [2].Resuscitation in septic shock aims t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…Interestingly, when MAP was used rather than SBP, we found that a threshold below 95 mmHg was associated with PIH. Thus, perhaps aiming for a higher perfusion pressure in the critically ill, either via MAP or SBP would prevent PIH and associated poor outcomes [32]. This would need to be tested via a future interventional trial.…”
Section: Plos Onementioning
confidence: 99%
“…Interestingly, when MAP was used rather than SBP, we found that a threshold below 95 mmHg was associated with PIH. Thus, perhaps aiming for a higher perfusion pressure in the critically ill, either via MAP or SBP would prevent PIH and associated poor outcomes [32]. This would need to be tested via a future interventional trial.…”
Section: Plos Onementioning
confidence: 99%
“…The Surviving Sepsis Campaign (SSC) guidelines [ 5 ] call for an initial MAP target of 65 mmHg for patients with septic shock, followed by individual titration of vasopressor agents. Although there is a general consensus that MAP should be maintained > 65 mmHg [ 5 8 ], there is debate regarding need for higher MAP targets in some patients [ 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the evidence, inclusion of patient preferences, and clear practical guidance should hopefully cut the usual lag time in knowledge translation and encourage early adoption. The move towards “aim for normality, or tolerance of near-normality” also ties into a large body of recent critical care work 161718. The message is becoming more and more familiar, and harder to ignore.…”
mentioning
confidence: 99%